ACCESS TO PROFESSION OF MEDIATOR IN GEORGIA: GENDER, EDUCATION, AND OTHER DIMENSIONS - Devadze Ketevan (Legal Bulletin, 2021)
In this article, we discuss the profession of the mediator, what kind of requirements or restrictions are pre- scribed for professional mediators in different countries, how different characteristics of a mediator can affect the mediation process or the outcome of the mediation. The article provides review and the comparative analysis of eligibility criteria for access to the profession of mediator set by the law in Georgia and other countries with further survey of Georgian mediators’ gender and education based on the official data of Unified Register of Mediators in Georgia. The analysis of the data that includes 54 medi- ators shows that 57,4% of mediators are female and that most mediators have a degree in law (88.8%). Other fields of education are Psychology (7,4%), Economics(1.8%), and Public relations (1.8%).